Adaptation of the Climate Change Perception Scale into Turkish: A Study of Validity and Reliability - Ediz, Çiçek; Yanık, Derya; Uzun, Sevda; Dinçer, Aytap; Yıldız, Güzel Nur (Ankara University, 2026)
Effective management of climate change is possible not only through scientific and technological solutions but also by understanding individuals’ perceptions and attitudes. The aim of this study was to adapt the Climate Change Perception Scale (CCPS) into Turkish and to examine its validity and reliability. The scale evaluates climate change perception through beliefs about the reality and causes of climate change, as well as the perceived importance (value) of its consequences, regional distance (where the impacts occur), and temporal distance (when the impacts will emerge). Data were collected from individuals aged 18 and above living in Türkiye using the snowball sampling method. The factor structure of the scale was assessed through confirmatory factor analysis, while reliability was evaluated using Cronbach’s alpha coefficient and item– total correlations. The original 14 items and five subdimensions were retained. CFA results confirmed that the scale has a five-factor structure consisting of “Reality,” “Causes,” “Value of Consequences,” “Regional Distance,” and “Temporal Distance.” The fit indices were found to be x2=164.731, df=66 (p<0.001), CMIN/df=2.496, GFI=0.920, AGFI=0.873, CFI=0.967, RMSEA=0.076, RMR=0.079, SRMR=0.0415, NFI=0.946, TLI=0.954, and IFI=0.967. The overall Cronbach’s alpha coefficient of the scale was 0.922, ranging from 0.686 to 0.950 for the subdimensions. In conclusion, the CCPS demonstrated a culturally adapted structure for individuals aged 18 and above in Turkish society and was found to be a valid and reliable measurement tool for assessing climate change perception. © 2026, Ankara University. All rights reserved.
İklim Değişikliği Algısı Ölçeği’nin Türkçe Uyarlaması: Geçerlik ve Güvenirlik Çalışması
Keywords: Climate Change; Climate Crisis; Perception; Reliability Scale Adaptation; Turkish Culture; Validity